Liquefaction susceptibility of beach sand containing plastic fines - Saeed, Hamza; Nalbantoglu, Zalihe; Uygar, Eris (Taylor & Francis Inc, 2023)
Liquefaction of saturated sand containing fines can be triggered due to propagation of seismic waves or by monotonically increasing loads. In such circumstances excess pore-water pressure development results in loss of confinement and decreased intergranular force transfer, leading to strain-softening behaviour. This research assesses the effect of plastic fines on the liquefaction susceptibility of carbonate sand from Famagusta Bay, Cyprus (Mediterranean Region). The study simulates the diverse composition of sand by incorporating varying proportions of silt and clay. Consolidated undrained triaxial compression tests were conducted to analyse the effect of fines on stability/instability, compressibility and location of critical state lines at low-stress levels of 50, 100 and 150 kPa with relative densities of 35% and 70%. Silt and clay fractions (10, 20, 30%) were incorporated into the sand to form a set of mixed soils. Sand and clayey-silty sand (10%) specimens prepared at loose state exhibited flow behaviour whereas diverse behaviour is observed for other soil groups. The prevention of instability can be attributed to the mineralogical nature of fines that amalgamated the soil structure.
Keywords: Beach sand; critical state; sand with fines; static liquefaction; triaxial test